Deformation of Precision Parts in Diesel Fuel Equipment During Diffusion Metallization - M. N. Erokhin; S. P. Kazantsev; A. G. Pastukhov; D. M. Skorokhodov; K. M. Logachev (Сельскохозяйственные машины и технологии)
The deterioration of the plunger working surfaces and sleeve worsens the economic and environmental performance of the diesel engine. Therefore, restoring the performance of worn plunger pairs with an increase in their wear resistance is economically feasible. The problem is proposed to be solved by the method of diﬀusion metallization to obtain hardening coatings based on iron carbides, nitrides and borides and alloying elements. (Research purpose) To evaluate the eﬀect of temperature regimes on the deformation of the plungers during diﬀusion boriding. (Materials and methods) The following parameters of the technological process are accepted: the composition of the powder mixture, the temperature and exposure time, the cooling time of the containers, the thickness of the coating, the deﬂection of the part. The materials under research are 45steel, KhVG steel, 25Kh5MA steel after nitriding in dissociated ammonia at the fuel equipment manufacturer. (Results and discussion) The thickness of the boride layer obtained after 8-hour boriding is 250; 215 and 170 micrometers, respectively. It is found that every 2 hours of the process result in an average layer increment of 40 microns. The average deﬂection of the plungers, exposed to 2-hour and 6-hour boriding, is 9.8 and 12.7 micrometers after the 8-hour cooling of containers. It is found that an increase in the cooling rate of the container leads to an increase in the warping of the plungers up to 35 microns. For uniform heating, it is recommended to use containers containing no more than 100 plungers. (Conclusions) The main reason for the deformation (deﬂection) of plungers after diﬀusion metallization is detected to be the relaxation of internal stresses in the core of the part as a result of structural changes in the steel. It is established that the minimum cooling time of the containers together with the furnace should be at least 8 hours. In this case, the deﬂection does not exceed 20 micrometers. It has been made possible to reduce the allowance for mechanical processing of the plunger to 30 microns.